Unveiling charge-transfer dynamics at singlet fission layer/hybrid perovskite interface - Xiao, Xingchi (2023)
Singlet fission (SF) materials have been applied in various types of solar cells to pursue higher power conversion efficiency (PCE) beyond the Shockley-Queisser (SQ) limit. SF implementation in perovskite solar cells has not been successfully realized yet due to the insufficient understanding of the SF/perovskite heterojunctions. In this work, we attempt to elucidate the charge dynamics of an SF/perovskite system by incorporating a well-known SF molecule, TIPS-pentacene, and a triple-cation perovskite Cs0.05(FA0.85MA0.15)0.95PbI2.55Br0.45, owing to their well-matched energy structures. The transient absorption spectra and kinetic fitting plots suggest an electron-transfer process from the triplet state of TIPS-pentacene to perovskite in the picosecond regime, which increases the carrier density by 20% in the perovskite layer. This work confirms the existence of an electron-transfer process between the SF material and perovskite, providing a pathway to SF-enhanced perovskite solar cells.